THE IMPORTANCE OF THE MONTESSORI PROGRAM IN THE SOCIAL DEVELOPMENT OF CHILDREN OF PRESCHOOL AGE (Proceedings of International Educators Conference, 2023)
This article is about the Montessori program and its advantages and disadvantages, and general information about this program is covered in detail in this article. The essence of this program is self-education of the child. The history and importance of Montessori today is also covered in this article.